Možnosti financování jednotlivých činností ve stavebním podniku - Solnický, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Předmětem bakalářské práce „Možnosti financování jednotlivých činností ve stavebním podniku“ je popis a hodnocení finančního řízení ve středně velké stavební společnosti. První část se v teoretické rovině zaobírá strukturou podnikového financování, finanční analýzou a definicí finančního plánování. V druhé části se aplikují teoretické poznatky do praxe. Nejprve je provedena finanční analýza stavebního podniku, která je pomocí vhodně vybraných ukazatelů vyhodnocena. Na základě evaluace analýzy je navržen plán financování pro nadcházející hospodářské období.

The subject of the bachelor’s thesis "Possibilities for Financing of Individual Activities in the Construction Company" is a description and assessment of financial management in a medium sized construction company. The first part deals with the theoretical structure of corporate finance, financial analysis and the definition of financial planning. The second part applies the theoretical knowledge into practice. First, the financial analysis of the construction company is performed, which is then evaluated using appropriately chosen parameters. Based on the evaluation of the analysis, a financing plan is proposed for the upcoming fiscal period.
Possibilities for Financing of Individual Activities in the Construction Company
Keywords: finanční řízení; financování podnikových činností; finanční analýza; finanční plánování; finanční ukazatele; rentabilita; aktivita; zadluženost; likvidita; financial management; financing of corporate activities; financial analysis; financial planning; financial ratios; profitability; activity; leverage; liquidity